PERBAIKAN TEKNIS BUDIDAYA KELAPA RAKYAT DI KABUPATEN WAJO - Nasaruddin, .; BDR, Muh. Farid; Ridwan, Ifayanti; Mollah, Abdul; Dariati, Tigin; Yanti, Cri Wahyuni Brahmi; Sukendar, Nandi K. (Jurnal Dinamika Pengabdian, 2020)
Coconut Plant is one of the annual plantations which is generally managed in the form of People's Plantation. Coconut plays an important role in the economic, cultural and social life of rural communities as a Heaven plant and a hundred uses plant. Coconut as a source of income for farming families in rural areas, can produce wealth and improve the quality of life in rural communities. Coconut plantations are generally managed on a small scale and are an important contributor to food security. At the industry level, coconut products have high added value and are an important source of employment and income for rural communities. Coconut oil is consumed by the wider community as food and as a raw material for the chemical industry, making soap, margarine and other products of high economic value. The level of management of smallholder coconuts is still very low and unsustainable so productivity is very low. To improve the productivity of smallholder coconuts, it is necessary to improve plant management systems so that they can be sustainable and can provide better added value.Keywords: Coconut, smallholder plantations, cultivation techniques. ABSTRAKTanaman Kelapa merupakan salah satu tanaman perkebunan yang bersifat tahunan yang pada umumnya dikelola dalam bentuk Perkebunan Rakyat. Kelapa memainkan peran penting dalam kehidupan ekonomi, budaya dan sosial masyarakat pedesaan sebagai tanaman surga dan tanaman seratus kegunaan. Kelapa sebagai sumber pendapatan bagi keluarga tani di pedesaan, dapat menghasilkan kekayaan dan meningkatkan kualitas hidup masyarakat di pedesaan. Perkebunan kelapa umumnya dikelola dalam skala kecil merupakan kontributor penting bagi ketahanan pangan. Di tingkat industri, produk kelapa bernilai tambah tinggi dan merupakan sumber lapangan pekerjaan dan pendapatan penting masyarakat pedesaan. Minyak kelapa dikomsumsi masyarakat luas sebagai makanan dan sebagai bahan baku industri oleokimia, pembuatan sabun, margarine dan produk  lainnya bernilai ekonomi tinggi. Tingkat pengelolaan tanaman kelapa rakyat sampai saat ini masih sangat rendah dan tidak berkelanjutan sehingga produktivitas yang dicapai sangat rendah. Untuk memperbaiki produktivitas tanaman kelapa rakyat diperlukan perbaikan sistem pengelolaan tanaman agar dapat berkelanjutan dan dapat memberikan nilai tambah yang lebih baik.Kata kunci: Kelapa, perkebunan rakyat, teknis budidaya.